2004
DOI: 10.1002/ca.10239
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mastectomy chylous fistula: Anatomical and clinical implications

Abstract: A chylous fistula after a modified radical mastectomy is a rare occurrence; however, major anatomical variations in the termination of the thoracic duct may occur, rendering it susceptible to injury. High output chylous fistulae are difficult to manage and have local, metabolic, and immunologic complications with a mortality rate varying from 12.5-50%. Herein such a case of postmastectomy chylous fistula and its management are discussed. A 56-year-old postmenopausal woman with invasive duct carcinoma of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Only studies from the last 8 years that were published in English were included. [6][7][8][9][10][11][12][13] It was concluded that most chylous leakage occurred on the left side, and only two of the pooled cases occurred on the right side. Level II or III axillary dissection was performed in 20 cases (our 4 cases included).…”
Section: Discussionmentioning
confidence: 99%
“…Only studies from the last 8 years that were published in English were included. [6][7][8][9][10][11][12][13] It was concluded that most chylous leakage occurred on the left side, and only two of the pooled cases occurred on the right side. Level II or III axillary dissection was performed in 20 cases (our 4 cases included).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, b chyle leakage subsided spontaneously by simply leaving the drain in situ [1][2][3]. Treatment of the chyle leakage required surgery in 2 cases [4,5]. In our case, chyle leakage subsided spontaneously by simply leaving the drain.…”
Section: Resultsmentioning
confidence: 56%
“…Purkayastha et al [5] observed chyle leakage at the time of its surgical repair at level I. A more aggressive dissection may not necessarily put the patient at an increased risk of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…contrary to popular belief electrocautery revealed to be a contributing factor increasing incidence of seroma, and as regards to arm movement some found benefit of delaying arm movement depending on that chest wall motion and shoulder use create shearing forces that hinders flap adherence and this will act as a pump forcing lymph into the empty axillary fossa [10], however others have found no benefit of delaying arm movement [11] [12].…”
Section: Discussionmentioning
confidence: 99%